Kelola Sampah, Selamatkan Bumi: Penyuluhan 3R (Reduce, Reuse, Recycle) Mewujudkan Lingkungan Berkelanjutan - Pertiwi, Fitri; Siregar, Herlina (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
The implementation of outreach activities to the community is motivated by low public awareness of environmental cleanliness. Awareness in waste management, especially household waste, still needs to be increased. Lopang urban village, especially Taman Lopang Indah neighbourhood 11, is an area that faces problems in managing household waste. The lack of concern among residents in managing waste and the absence of final disposal sites have resulted in waste not being properly organized and often scattered around. This outreach activity aims to increase public awareness in neighbourhood 11 Lopang urban village regarding the importance of managing household waste by applying the 3R principle (Reduce, Reuse, Recycle). The lack of public understanding of the 3R concept is caused by a lack of support and involvement from both the community and government in facilitating waste management. This problem is the main focus that needs to be resolved through outreach activities aimed at providing an understanding of the 3R concept and its implementation in everyday life. In this way, it is hoped that waste management habits will be formed which can contribute to improving the culture of waste management in the community. This activity was carried out at the Al-Fath Mosque, neighbourhood 11, Lopang urban village. After attending education regarding waste management, the public understands better the importance of waste management and sorting. In fact, the community is starting to plan to establish a waste bank as a concrete step in improving waste management in the area.